Clinical, microscopic and mechanical evaluation of expanded skin in horses following subcutaneous implantation with anisotropic tissue expanders - Saleh, Saddam Hussein Mohammaed (2022)
Skin expander is a surgical an implant used to stretch cutaneous tissues through a combination of creep and biological stretch processes in other to generate extra cutaneous tissues for potential use in reconstructive skin surgeries. The understanding of the mechanical and histological features of expanded skin in horses is an important step to validate the use of tissue expander for skin extension in skin defect repair in horses. Therefore, this study aims to evaluate the clinical, mechanical, and histological properties of expanded skin following implantation of unidirectional anisotropic subcutaneous tissue expanders at different locations of horse’s skin. In addition to that, possible behavioural changes in horses post tissue expander implantations were also investigated. A total of six horses were surgically implanted subcutaneously with unidirectional anisotropic tissue expanders at three different locations: the frontal region of the head, lateral side of the right shoulder, and dorsomedial part of the cannon region of the right forelimb. Each horse was clinically examined, and behaviour patterns were recorded in the stable box during the day and night-time, three days prior to - and six-days post implantation. After 14 days of subcutaneous expansion, skin biopsies of the expanded skin and representative normal skin samples from all the regions were collected. A part of each sample was subjected to mechanical properties study while the remaining was used for histological and immunohistochemical study. All horses tolerated the tissue expander implantation with no effect on the vital parameters as well as the overall horse behaviour. The mechanical properties of expanded skin from the shoulder area showed higher (11.57±1.23 MPa) elastic modulus (EM), maximum stress (MSs) (17.54±3.45 MPa), maximum strain (MSr) (177.70±58.53 %), and maximum force (MF) (150.70±59.89N), than the normal skin when compared to the forehead and lower forelimb. The overall effect of locations on EM and MSs was statistically significant (p < 0.05), however, there was no overall effect of horse factor, treatment factor (normal and expanded skin), and location interaction on the EM, MSS, MF, and MSr. The locations of the expanded or normal skin has effect on the EM and MSs with expanded skin from the frontal and distal limb areas been stiffer (less elastic) and need higher force to failure compared to the expanded skin of the shoulder. Histological evaluation revealed an increase in the thickness of the epidermal, dermal, and total skin layers with up regulation of vascular endothelial growth factor (VEGF) expression in the expanded skins. There was no significant difference in the histo-morphometric data between the three locations. The collagen fibres were more loosely packed in the expanded skin samples. The expression of VEGF was higher in the expanded skin than the normal skin. In conclusion, the implantation of unidirectional anisotropic subcutaneous tissue expanders in horses resulted in successful skin expansion with no physiological and behavioural discomfort. These findings will serve as important information when tissue expansion technique is to be applied in horses for skin reconstructive surgery according to anatomical regions. In general, skin expansion technique is considered a good technique to generate additional cutaneous tissue for equine skin reconstructive surgery.